Prognostic role of cardiac troponin I after percutaneous coronary intervention in stable coronary disease. Issue 9 (15th August 2005) - Nageh, T; Sherwood, R A; Harris, B M; Thomas, M R
Abstract : Objective: To assess the role of cardiac troponin I (cTnI) in predicting outcome after percutaneous coronary intervention (PCI). Methods and results: cTnI was measured immediately before and at 6, 14, and 24 hours after PCI in 316 consecutive patients with stable symptoms and native coronary artery disease. The study end point was the occurrence of major adverse cardiac events (MACE) at 30 days and at 18 months after PCI: death, Q wave myocardial infarction (MI), or repeat revascularisation in hospital. Postprocedural cTnI increased in 31% of patients. The cumulative MACE rate at 18 months was 25% (17.7% due to repeat PCI procedures). There was a significant association between postprocedural cTnI increase and death, Q wave MI, or both (odds ratio (OR) 3.28, 95% confidence interval (CI) 1.7 to 6.4, p  =  0.01). Post-PCI cTnI increase had a positive predictive value (PPV) for adverse events at 18 months of 0.47 and a negative predictive value (NPV) of 0.96 (OR 18.9, 95% CI 9.7 to 37, p < 0.0001). The presence of both a postprocedural cTnI rise and a procedural angiographic complication gave a PPV for adverse events of 0.69 and an NPV of 0.92 (OR 22.6, 95% CI 2.6 to 68.6, p  =  0.0005). Conclusions: cTnI increased post-procedurally in one third of this stable patient population undergoing elective PCI and was independently and significantly predictive of an increased risk of adverse events at 18 months, predominantly in the form of repeat PCI.